Mononuclear and Heterobimetallic Complexes of Palladium(II) with 4,5-Diphenyl-1,2,4-triazole-3-thione - H. ABDULLAH, BAYAZEED; A. AL-JIBORI, SUBHI; A. ABDULLAH, MOHAMED; A. K. AL-ALLAF (Deceased), TALAL (Asian Journal of Chemistry, 2010)
The reaction of Na2PdCl4 with 4,5-diphenyl-1,2,4-triazole-3-thione (LH) in acetone gave cis-[PdCl2(LH)2]. Stirring cis-[PdCl2(LH)2] in methanol gave a diamagnetic cis-[PdL2]. Reaction of cis-[PdL2] with diphosphines gave diamagnetic complexes of the type [PdL2(diphos)] where diphos = 1,2-bis(diphenylphosphino)methane (dppm), 1,2-bis(diphenylphosphino) ethane (dppe) or 1,2-bis(diphenylphosphino)-propane (dppp). The complexes cis-[PdCl2(LH)2] and cis-[PdL2(diphos)] have been used effectively to prepare bimetallic complexes of the type cis-[Cl2Pd(μ-LH)2M´Cl2] where M´ = Co, Ni, Mn or SnCl2 and [(diphos)Pd(μ-L)2M´Cl2] where M´ = Co or Ni, the prepared complexes were characterized by elemental analysis, magnetic susceptibility, IR, UV-Vis, 1H and 31P-1H NMR spectral data.